Assertive Behavior Development for Drug Abuse Prevention through Group Guidance Services - Putri Gusti Maulinsari; Diana Septi Purnama (STAI Hubbulwathan Duri, 2022)
This study aims to determine one kind of student attitude that must be developed by students to avoid drug abuse, namely assertiveness. To develop assertiveness, counseling teachers/counselors can train them in group guidance services. This study used an experimental method with one group pre-test and post-test design, the sample used was students who have low scores on assertive behavior. Data were collected using a questionnaire assertive instrument with a Likert scale. This study contains the analysis using a statistical t-test. The results showed that the influence of group counseling services on assertive behavior for the prevention of drug abuse with t-count (7.043) t table (1.83) with = 0.05.